Strategic Management: A Policy To Enhance Sustainable Business Development In Small And Medium Scale Enterprises In Nigeria - Adeyemi, Irefin Isaac; Isaac, Oyebola Abiodun; Olufemi, Akintelu Sunday (Archives of Business Research, 2017)
The paper examined the impact of Strategic Management on the performance of Small and Medium Scale Enterprises (SMEs) via competitive advantage, sales and profit. This was with the view of assessing the impact of Strategic Management on sustainable growth in Nigerian SMEs. A descriptive survey research design was employed for the paper using structured questionnaire and oral interview for data collection. The questionnaire was administered on thirty SMEs owners in four states of Southwest Nigeria comprising Lagos, Ogun, Osun and Oyo State. Thus, a total of 120 respondents were purposively sampled for the study. Data collected were analyzed using frequency tables, simple percentages and chi-square test. The results showed that Strategic Management practices significantly assist SMEs to gain competitive advantage ( The results further showed that Strategic Management significantly increased their sales ( and improved their profits levels. The paper concluded that, Strategic Management has contributed immensely to the sustainable growth of Small and Medium scale Enterprises in South-West Nigeria and recommended that Strategic Management practice should be adopted by all small and medium business firms in Nigeria.